Tourism Governance Studies: A Bibliometric Analysis - Loso Judijanto (Westscience Press, 2026)
Research on tourism governance has been gaining increasing popularity as tourism development has been growing more complicated and needs better coordination between various parties. This paper attempts to analyze the intellectual structure, research development, and new trends of tourism governance through bibliometric analysis. The data were obtained from the Scopus database via specific keywords relating to tourism governance, destination governance, and tourism policy, after which the data were analyzed via VOSviewer in order to conduct analysis on publication trends, keyword co-occurrence, citation networks, influential authors, institutional collaboration, and country collaboration. It was found out that research in tourism governance has undergone considerable development, the most prominent research themes being sustainable tourism, tourism development, stakeholder collaboration, ecotourism, destination management, conservation, and local involvement. Keyword analysis has shown the evolution from a traditional governmental model of tourism management towards a collaborative one. Citation analysis highlights influential contributions focusing on governance frameworks, sustainable tourism policy, community-based tourism, and conservation management, with scholars such as Hall, Bramwell, Dredge, and Jamal providing important theoretical foundations. Furthermore, the collaboration analysis demonstrates that tourism governance research has become a global field involving strong academic networks across countries, particularly the United Kingdom, China, and the United States. This study contributes to a deeper understanding of the development trajectory of tourism governance research and identifies future research opportunities related to smart tourism governance, climate resilience, digital transformation, and inclusive destination management.